An examination of the place of school mathematics in preparing pupils for the workplace in Antigua and Barbuda - Weston, Caron Olivene (2014)
This research examines the preparation made to enable mathematics teachers to appropriately prepare school leavers entering directly into the workforce upon graduation to handle the different branches of mathematics. The methodology was that of the interpretive qualitative paradigm. The method was that of the multi method case study and the tools included: constructed conversation; interviews; telephone calls; email; focus group; photography; video recording; participatory observation; observation and documentation. The theoretical framework was informed by components of the Engeström (2001) second generation model.